Transcriptome and metabolome analyses of Coilia nasus in response to Anisakidae parasite infection. Issue 87 (April 2019) - Liu, Kai; Yin, Denghua; Shu, Yilin; Dai, Pei; Yang, Yanping; Wu, Hailong
Abstract: Parasites from the family Anisakidae are capable of infecting a range of marine fish species worldwide. Coilia nasu s, which usually feeds and overwinters in coastal waters and spawns in freshwater, is highly susceptible to infection by Anisakidae. In this study, we used scanning electron microscopes to show that C. nasu s infected by Anisakidae exhibited damage and fibrosis of the liver tissue. To better understand host immune reaction and metabolic changes to Anisakidae infection, we used a combination of transcriptomic and metabolomic method to characterize the key genes and metabolites, and the signaling pathway regulation of C. nasus infected by Anisakidae. We generated 62, 604 unigenes from liver tissue and identified 391 compounds from serum. Of these, Anisakidae infection resulted in significant up-regulation of 545 genes and 28 metabolites, and significant down-regulation of 416 genes and 37 metabolites. Seventy-four of the 961 differentially expressed genes were linked to immune response, and 1, 2-Diacylglycerol, an important immune-related metabolite, was significantly up-regulated after infection. Our results show activation of antigen processing and presentation, initiation of the T cell receptor signaling pathway, disruption of the TCA cycle, and changes to the amino acid and Glycerolipid metabolisms, which indicate perturbations to the host immune system and metabolism following infection. This is the first study describing the immune responses and metabolic changes in C. nasus to Anisakidae infection, and thus improves our understanding of the interaction mechanisms between C. nasus and Anisakidae. Our findings will be useful for future research on the population ecology of C. nasus. Highlights: Microscopic observation showed that C. nasu s infected by Anisakidae exhibited damage and fibrosis of the liver tissue. We profiled the differences in gene and metabolite expression between control and Anisakidae-infected C. nasu s. We generated 62, 604 unigenes from liver tissue and identified 391 compounds from serum. Anisakidae infection resulted in several major perturbations to the host immune responses and to metabolic changes. These data will be useful for future research on population ecology of C. nasus.